Targeting Heterochromatin Formation to Transposable Elements in Drosophila: Potential Roles of the piRNA System. - Sentmanat, M.; Wang, S.H.; Elgin, S.C. (Biokhimiya, 2013)
Successful heterochromatin formation is critical for genome stability in eukaryotes, both to maintain structures needed for mitosis and meiosis and to silence potentially harmful transposable elements. Conversely, inappropriate heterochromatin assembly can lead to inappropriate silencing and other deleterious effects. Hence targeting heterochromatin assembly to appropriate regions of the genome is of utmost importance. Here we focus on heterochromatin assembly in Drosophila melanogaster, the model organism in which variegation, or cell-to-cell variable gene expression resulting from heterochromatin formation, was first described. In particular, we review the potential role of transposable elements as genetic determinants of the chromatin state and examine how small RNA pathways may participate in the process of targeted heterochromatin formation.